Agro-Based Biocomposites for Industrial Applications - Leão, Alcides Lopes [UNESP]; Souza, S. F. [UNESP]; Cherian, B. M. [UNESP]; Frollini, E.; Thomas, S.; Pothan, L. A.; Kottaisamy, M. (Taylor & Francis Ltd, 2010)
Leaf fibers are fibers that run lengthwise through the leaves of most monocotyledonous plants such as pineapple, banana, etc. Pineapple (Ananas comosus) and Banana (Musa indica) are emerging fiber having a very large potential to be used for composite materials. Over 150,000 ha of pineapple and over 100,000 ha of banana plantations are available in Brazil for the fruit production and enormous amount of agricultural waste is produced. This residual waste represents one of the single largest sources of cellulose fibers available at almost no cost. The potential consumers for this fiber are pulp and paper, chemical feedstock, textiles and composites for the automotive, furniture and civil construction industry.
Keywords: Composites; nanocellulose; natural fibers; PALF; pineapple